Ruthenium‐Catalyzed Transfer‐Hydrogenative Cyclization of 1, 6‐Diynes with Hantzsch 1, 4‐Dihydropyridine as a H2 Surrogate. Issue 36 (25th July 2013) - Yamamoto, Yoshihiko; Mori, Shota; Shibuya, Masatoshi
Abstract The transfer‐hydrogenative cyclization of 1, 6‐diynes with Hantzsch 1, 4‐dihydropyridine as a H2 surrogate was performed in the presence of a cationic ruthenium catalyst of the type [Cp′Ru(MeCN)3PF6]. Exocyclic 1, 3‐dienes or their 1, 4‐hydrogenation products, cycloalkenes, were selectively obtained, depending on the substrate structure and the reaction conditions.